Analisis Faktor Resiliensi Rumah Tangga Petani dalam Menghadapi Variabilitas Iklim - Marseva, Amalia Dwi; Putri, Eka Intan Kumala; Ismail, Ahyar (Jurnal Ekonomi dan Pembangunan Indonesia, 2016)
Climate variability potentially giving shocks to farmers household. This research aims to identify farmers household vulnerability, identify factors affecting resilience, and identify the adaptation mechanism of farmers household in facing rainfall variability. The analytical methods are descriptive analysis, Livelihood Vulnerability Index, and multiple regression. Results shows that Sidamulya is more vulnerable than Wanasari. Households has low resilience. Factors that affecting resilience are education, earning level, number of years in farming, and dummy other job. Adaptive mechanisms are shifting the planting time, replace and decrease fertilizer, replace seed, and move to another job.